Establishment of a protein thermal shift chip (PTSC) for COVID-19 and exploration of the future of protein chips in pharmacology - Peng Chen; Zhao Cui; Caifeng Li; Shiwen Deng; Hongjun Yang (Compuscript Ltd, 2022)
Traditional protein chips are based on solid chips and cannot enable drug and target screening in a label-free manner. Herein, a protein thermal shift chip (PTSC) based on fluorescence signals is proposed, which enables low-cost, high-throughput, label-free screening. We developed a PTSC for COVID-19, containing 12 SARS-CoV-2 and host target proteins. A series of quality-control tests were performed for small-molecule drugs, macromolecular antibodies, and herbal-medicine extracts. This chip enabled high-throughput screening of COVID-19 drugs and thus may serve as a tool for screening drug targets clinically effective drugs.